Gestão de portfólio de produtos em pequenas empresas de base tecnológica - Leoni, Juliene Navas [UNESP]; Jugend, Daniel [UNESP]; Silva, Mila Gibran [UNESP]; Salgado, Manoel Henrique [UNESP]; da Silva, Sérgio Luis (My University, 2014)
The product portfólio management is considered relevant activity to the proper performance of the product development process. This paper aims to present the main methods of management that technology-based small businesses adopt for decision-making in product portfolio. This survey, which collected data on 31 companies was conducted. It was observed that although firms adopt market research and mapping methods and financial methods and for this decision-making, most of them based on the informal deliberations of senior management. Unable to understand the business relationships between the presence of ISO 9001 certification with greater formalization for decision making in product portfolio.
Product portfolio management in small high-tech companies
Keywords: High-tech companies; Methods for decision making; Product portfolio management